(untitled) (Medico Legal Update, 2020)
Klebsiella pneumoniae is an opportunistic pathogen causing nosocomial infections with production of biofilm. In the current study, 73 samples were collected from both patient genders of different ages suffering of burn and wound injuries that referred to four hospitals in Baghdad city from Aug. to Nov. 2019. The samples were cultured on MacConkey agar and 60 bacterial isolates were obtained. Primary identification by cultural and microscopic examinations declared that all isolates belong to genus Klebsiella. Then the 60 isolates were identified by Vitek 2 system which insured they were belonged to Klebsiella pneumoniae. The identified isolates were screened for ability to produce biofilm by Microtiter Plate technique and Congo red agar method. Results showed that only 4 isolates (3 of wounds and 1of burns) were able to form biofilms. Upon such important characteristic, the four isolates were submitted to the 16S rRNA gene amplification test by using PCR technique and results declared that they are certainly belong to Klebsiella pneumoniae. The “National Center for Biotechnology Information (NCBI)” verified and documented that they are new strains of Klebsiella pneumoniae to be discovered in this study for the first time and registered them as; KPWIQ25, KPWIQ49, KPWIQ51 and KPBIQ19 strains of Klebsiella pneumoniae.